Guillain-Barré syndrome (GBS) complicated by rhabdomyolysis (RML): Case reports of 2 children and literature review - Yang, Xin-Ying; Han, Tong-Li; Lv, Jun-Lan (Frontiers in Pediatrics, 2022)
We first describe two children Guillain-Barré syndrome (GBS) patients with rhabdomyolysis（RM）and review five adult patients from the literature. Through the analysis of clinical, laboratory examination, treatment and prognostic data from these seven patients, we found that when GBS “meets” RM, male dominance was obvious；limb weakness, pain and respiratory failure may be caused by multiple factors; limb weakness and respiratory muscle paralysis are more serious than with GBS alone; and the probability of mechanical ventilation is increased. Neuroelectrophysiological studies revealed axonal lesions. Close monitoring and timely identification of serious fatal complications such as electrolyte disorder, internal environment disturbance and kidney injury is essential. Plasma exchange, peritoneal dialysis and supportive treatment were actively adopted. The long-term outcome of most patients is satisfactory.